CULTURAL BRANDING SEBAGAI STRATEGI PENGUAT HUBUNGAN ANTARA DIGITAL MARKETING DAN BUSINESS MODEL EXPERIMENTATION TERHADAP BUSINESS SUSTAINABILITY UKM - Elvina Adi Saputri, Luh Gede; Mulyadi, Made (Penerbit Lafadz Jaya, 2025)
This study analyzes the role of cultural branding as a strategy to strengthen digital marketing relationships and business model experimentation in SMEs. The study population was wood, silver, and endek craftsmen in Bali Province. The exact population size was unknown, so the sample size was determined purposively at 125 SMEs. A five-point Likert-scale closed-ended questionnaire was used as the data collection tool. Data were analyzed using descriptive and inferential statistics assisted by SEM-PLS software. Produced seven findings: 1) Cultural branding partially mediates the influence of Digital marketing on Business sustainability. 2) Cultural branding partially mediates the influence of Business model experimentation on Business sustainability. 3) Digital marketing has a significant positive effect on Business sustainability. 4) Business model experimentation has a significant positive effect on Business sustainability. 5) Cultural branding has a significant positive effect on Business sustainability. 6) Digital marketing has a significant positive effect on Cultural branding. 7) Business model experimentation has a significant positive effect on Cultural branding. Since Cultural branding is only a partial mediation, the presence of Cultural branding in the model is not absolutely necessary. However, the presence of Cultural branding is quite positive. The involvement of Digital marketing, Business model experimentation and Cultural branding should be very necessary in creating Business sustainability.